Investment and Business Cycles: Focusing on Firms' Capital Adjustment Costs - Changwoo Nam (KDI Journal of Economic Policy, 2022)
This paper empirically verifies that the types of capital adjustment costs serve as an important mechanism in relation to investment decision- making after confirming that the investment dispersion of Korean firms is pro-cyclical and can affect busin ess cycles. Specifically, it is found through empirical methods using corporate financial data that capital adjustment costs generally assumed to take a quadratic form in macroeconomics are asymmetric and irreversible in the Korean economy. In particular, capital adjustment costs are empirically proven to cause investment dispersion to expand given that the substitution effect of the marginal value to the marginal cost for one unit of investment in the inter-temporal investment decision is affected by that cost with regard to the resale of owned equipment assets, as opposed to new investments in equipment assets. We ultimately show, albeit indirectly, that investment dispersi on can affect business cycles as capital adjustment cost s influences investment decisions. What is implied is that the capital adjustment cost is not merely an exogenously deep parameter that fits the dynamics of business cycles in a macroeconomic model but could instead be a policy variable that can be endogenized through government policies.
Keywords: C58; D24; D25; 330; Investment; Business Cycles; Capital Adjustment Costs; GMM